Enhancing Digital Entrepreneurship of the Kampung Durian Community through Ecopreneurship Training based on Artificial Intelligence in Pakis Village, Jember - Pamungkas, Zakaria Sandy; Sari, Eka Puspita Kartika; Sumiati, Ika Dewi; Utama, Aditya Satya; Salsabila, Nurista; Utami, Nita Dwi; Falupi, Yohana Dwi; Putri, Asyiah Ika (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2025)
Background: The Pakis village is known as the Durian Village which has abundant durian farming potential. However, the low skills of the community in product processing and digital marketing have not provided economic value. Contribution: This community service activity aims to enhance the digital entrepreneurship skills of the community through ecopreneurship based on Artificial Intelligence (AI). Method: This research used a descriptive qualitative approach combined with the Participatory Action Research (PAR) method with 20 purposively selected participants. Data were collected through pre- and post-tests, observations, focus group discussions, and interviews, and analyzed using thematic analysis supported by descriptive statistics. Results: Ecopreneurship training based on artificial intelligence significantly enhanced participants' digital entrepreneurship with pre-test score 41.2 and post-test score 88.1 with an improvement of 113.9%. Conclusion: The findings highlight the novelty of participatory integration between ecopreneurship and AI in rural contexts, offering both theoretical contributions to the literature on sustainable digital entrepreneurship and practical insights for policy. This model has potential for replication in other rural communities in Southeast Asia, supporting global discourses on the circular economy, digital inclusion, and the Sustainable Development Goals (SDGs).